2015 International Conference on Advances in Computing, Communications and Informatics (ICACCI) 2015
DOI: 10.1109/icacci.2015.7275808
|View full text |Cite
|
Sign up to set email alerts
|

Statistical features based epileptic seizure EEG detection - an efficacy evaluation

Abstract: Electroencephalographic (EEG) patterns are electrical signals generated in association with neural activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…2. Entropies based detection of an epileptic seizure using EEGs have been studied and well reported in the recent past (Srinivasan et al 2007;Pravin et al 2010;Aydin et al 2009;Wang et al 2011;Gopan et al 2015). Srinivasan et al (2007) have employed ApEn feature with REN network as a classifier and have achieved 100 % CA.…”
Section: Discussionmentioning
confidence: 99%
“…2. Entropies based detection of an epileptic seizure using EEGs have been studied and well reported in the recent past (Srinivasan et al 2007;Pravin et al 2010;Aydin et al 2009;Wang et al 2011;Gopan et al 2015). Srinivasan et al (2007) have employed ApEn feature with REN network as a classifier and have achieved 100 % CA.…”
Section: Discussionmentioning
confidence: 99%
“…The two similar works reported by Gopika Gopan et al [43][44] and another reported by Bhuvaneshwari et al [45], used various time domain statistical features such as energy, variance, entropy, median absolute deviation, interquartile range, kurtosis, skewness, and linear prediction coefficient. Khorshidtalab et al [46] also used time domain statistical features for their motor imagery classification problem by analyzing EEG signals.…”
Section: Feature Extraction and Feature Selectionmentioning
confidence: 99%